A expressão do sujeito pronominal em cartas e postais capixabas do século XX - Massariol, Caroliny Batista (2018)
The expression of pronominal subject in Brazilian Portuguese, theme of this essay, may occur in two different forms: filled, as observed on Vicente Caetano’s postcard, dated March 14th, 1954 (“eu poderia ir procurar”) or non-filled, as found on Oswald Guimarães’s letter, dated March 16th, 1919 (“Ø Irei assistir and Ø te contarei”). Both forms have their specificities of conditioning from one use to another dependent on each discourse subject. Several linguistics have studied this phenomenon, among them: Duarte’s (1993) analysis based on theatrical plays from Rio de Janeiro during the XIX and XX centuries stated that the expression of the pronominal subject in Brazilian Portuguese (PB) has been suffering modification, in which, the null or non-expressed subject opens way to the explicit pronominal expression. It is to given the grammaticalization of the pronouns você, vocês e a gente, fact that produces some rearranging on the chart of pronouns; Paredes Silva (1988) emphasizes the importance of studying the functional influences behind the explicit pronominal subject. As mentioned in previous studies, there is the hypothesis that this phenomenon undergoes conditioning, that is, it occurs a fill in the expression of the pronominal subject on certain occasions, due to internal and external motivations. To substantiate our hypothesis, we have done an analysis, according to the assumptions of the Theory of Language Variation and Language Change (LABOV, 2008 [1972]), in letters and postcards handwritten by two writers born in Espírito Santo throughout the XX century: Oswald Cruz Guimarães and Vicente Caetano. We analyzed the phenomenon from two perspectives: general analysis of the expression of the pronominal subject in the entire system and of each person of the singular discourse. We verified the influence of the following factors on the filled expression of the pronominal subject: emphasis, pronoun, ambiguity, style, structure of correspondence, change of reference, subject matter of the excerpts of the correspondences and, in the third person of the discourse, the subject's liveliness. With this study, we observed the variation of the expression of the pronominal subject used by writers from Espírito Santo, Brazil.